The Influence of Motivation and Job Satisfaction on Employee Performance - Sunardi, Didi; Awaliah, Ade Tuti (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the influence of work motivation and job satisfaction on employee performance at PT. Sumber Alfaria Trijaya Tbk. The research employs a quantitative approach using a multiple linear regression method. The population in this study includes all PT employees. Sumber Alfaria Trijaya Tbk, while the sample consists of 40 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using validity and reliability tests, classical assumption tests, and hypothesis testing through partial and simultaneous analysis. The results show that both work motivation and job satisfaction positively and significantly affect employee performance, either partially or simultaneously. These findings suggest that employee performance can be improved by increasing motivation and job satisfaction through organizational policies that support career development, reward systems, and a positive work environment. The research contributes to the field of human resource management by reinforcing the role of psychological factors in enhancing work performance.